Engineering practices for milk product : dairyceuticals, novel technologies, and quality - Goyal, Megh R. (ed.); Hati, Subrota, (ed.) (Ontario Apple academic press, 2021)
"While also addressing the need for more effective processing technologies for increased safety and quantity, the dairy industry needs to address the growing customer demand for new and innovative dairy foods with enhanced nutritional value. This volume, Engineering Practices for Milk Products: Dairyceuticals, Novel Technologies, and Quality, looks at new research, technology, and applications in the engineering of milk products, specifically covering functional bioactivities to add value while increasing the quality and safety of milk and fermented milk products. Chapters in the book look at the functional properties of milk proteins and cheese, functional fermented milk-based beverages, biofunctional yoghurt, antibiotic resistant pathogens, and other probiotics in dairy food products. The information found here will be of value to the growing dairy industry in India, globally the largest milk producing country since 1997, and the research will also be useful for dairy food engineering professionals wherever milk and dairy products are produced and consumed"--
Keywords: Dairy products--Quality--Research.; Dairy products industry--Technological innovations--Research.